Potato expressing beetle-specific Bacillus thuringiensis Cry3Aa toxin reduces performance of a moth - Hussein, Hany M; Habuštová, Oxana; Turanli, Ferit; Sehnal, František (Journal of chemical ecology, 2006)
Expression of the Bacillus thuringiensis beetle-specific toxin Cry3Aa, which renders a genetically modified potato cultivar resistant to the Colorado potato beetle Leptinotarsa decemlineata, exerts a deleterious effect on the polyphagous moth Spodoptera littoralis. The caterpillars of S. littoralis feed less and produce smaller pupae on the genetically modified cultivar (NewLeaf Superior) than on the parental nontransgenic cultivar (Superior). The conversion efficiencies of total dry matter, combustion heat, carbon, and nitrogen from leaves to insect biomass are similar on both cultivars. In spite of similar food utilization and a relatively small difference in the body mass at pupation, female adults that developed from caterpillars fed on NewLeaf Superior lay a mean of 309 eggs compared to a mean of 713 eggs deposited by females that developed from caterpillars fed on Superior. Because of this difference and a simultaneous reduction in fertility (egg hatchability) from 78 to 48%, a pair of adults that fed as larvae on NewLeaf Superior produces only 148 larvae, whereas a pair of adults that fed as larvae on Superior produces 556 larvae. We suggest that small amounts of Cry3Aa that accumulate in insect tissue and persist until the adult stage are responsible for the decline in reproduction.
Keywords: financování organizované; Animals; Solanum tuberosum; Female; Bacterial Toxins; ženské pohlaví; endotoxiny; bakteriální proteiny; Bacterial Proteins; rekombinantní proteiny; Hemolysin Proteins; Recombinant Proteins; hemolyziny; Endotoxins; Financing, Organized; Spodoptera; bakteriální toxiny; Larva; zvířata; larva